HUBUNGAN ASUPAN ENERGI PROTEIN DAN LAMANYA MENJALANI HEMODIALISA DENGAN STATUS GIZI PADA PASIEN GINJAL KRONIK DI RSUD PROF W.Z JOHANNES KUPANG - Benu, Lolang Loriana; Adi, Anak Agung Ayu Mirah (Poltekkes Kemenkes Kupang, 2025)
Chronic kidney disease (CKD) is considered a significant health challenge due to its increasing prevalence and poor prognosis. The incidence of chronic kidney disease in East Nusa Tenggara was 0.33% in 2018, while Kupang City had a lower prevalence of 0.45 %, according to Riskesdas. Based on data from the medical records section of RSUD.WZ. According to Johannes Kupang, the number of sufferers of chronic kidney disease in January-June 2023 was 44 people at RSUD W.Z.Johanes Kupang. This research method is included in the analytical descriptive research category which uses a cross-sectional framework. Findings Specifically, participants' energy expenditure (63.2%) fell into the